2006
DOI: 10.1128/mcb.26.5.1700-1709.2006
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Fibulin-4 Abolishes Elastogenesis and Causes Perinatal Lethality in Mice

Abstract: Elastic fibers provide tissues with elasticity which is critical to the function of arteries, lungs, skin, and other dynamic organs. Loss of elasticity is a major contributing factor in aging and diseases. However, the mechanism of elastic fiber development and assembly is poorly understood. Here, we show that lack of fibulin-4, an extracellular matrix molecule, abolishes elastogenesis. fibulin-4 ؊/؊ mice generated by gene targeting exhibited severe lung and vascular defects including emphysema, artery tortuos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
189
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(207 citation statements)
references
References 56 publications
12
189
0
2
Order By: Relevance
“…The elastic fibers contain irregular elastin aggregates with evenly distributed rod-like filaments visible within the usual amorphous globules. Elastin cross-links are greatly reduced, but the expression of tropoelastin and LOX is normal (McLaughlin et al, 2006). The rod-like filaments in the fbn42/2 elastic lamellae resemble those observed in the aorta of chicks fed b-aminopropionitrile (BAPN), an irreversible LOX inhibitor.…”
Section: Fibulinsmentioning
confidence: 98%
See 1 more Smart Citation
“…The elastic fibers contain irregular elastin aggregates with evenly distributed rod-like filaments visible within the usual amorphous globules. Elastin cross-links are greatly reduced, but the expression of tropoelastin and LOX is normal (McLaughlin et al, 2006). The rod-like filaments in the fbn42/2 elastic lamellae resemble those observed in the aorta of chicks fed b-aminopropionitrile (BAPN), an irreversible LOX inhibitor.…”
Section: Fibulinsmentioning
confidence: 98%
“…Fibulin-4 and/or -5 interact with these aggregates to facilitate cross-linking (McLaughlin et al, 2006) or to limit the aggregate size. The elastin aggregates remain on the cell surface long enough for new elastin to be secreted from the cell and added to the aggregates .…”
Section: Modelmentioning
confidence: 99%
“…A reduction in elastic fibers specifically in fascia connective tissues may explain the herniation phenotype. Mice lacking either fibulin-4 or fibulin-5 have highly disrupted and disorganized elastic fibers, leading to developmental defects in skin, arterial blood vessels, and lungs (13,14,27). Although the elastic fiber abnormalities are similar in these two mouse mutants, the fibulin-4 null mice are perinatally lethal, whereas the fibulin-5-deficient mice can survive until adulthood.…”
mentioning
confidence: 96%
“…Our immunohistochemical studies showed an upregulation of fibulin-4 expression in cervical carcinoma tissues, compared with normal cervical tissues and CIN. Fibulin-4 is rich in elastic fiber tissue, and is mainly involved in the synthesis and arrangement of elastic fibers (39). In the present study, the expression of fibulin-4 in the extracellular matrix was found Figure 4.…”
Section: Discussionmentioning
confidence: 55%